2005
DOI: 10.1074/jbc.m501113200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of CC3 (TIP30)

Abstract: CC3 (TIP30) is a protein with pro-apoptotic and antimetastatic properties. The tumor suppressor effect of CC3 has been suggested to result from inhibition of nuclear transport by binding to importin ␤s or by regulating transcription through interaction in a complex with co-activator independent of AF-2 function (CIA) and the c-myc gene. Previous biochemical studies indicated that CC3 has protein kinase activity, and a structural similarity to cAMP-dependent protein kinase catalytic subunit was proposed. By con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In addition, a group of NAD/NADP-dependent proteins, including NmrA, CC3, and C-terminal binding protein, has been shown to regulate gene transcription factors by sensing the cellular level of NAD/NADP (30,(47)(48)(49)(50). Our observation that HSCARG enters the nucleus subsequent to a change in the intracellular redox state, together with our data that overexpression of HSCARG leads to NFB inhibition, 3 suggested that HSCARG may also target nuclear proteins, such as transcription factors, to further counter-balance the effects of the decreasing NADPH concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a group of NAD/NADP-dependent proteins, including NmrA, CC3, and C-terminal binding protein, has been shown to regulate gene transcription factors by sensing the cellular level of NAD/NADP (30,(47)(48)(49)(50). Our observation that HSCARG enters the nucleus subsequent to a change in the intracellular redox state, together with our data that overexpression of HSCARG leads to NFB inhibition, 3 suggested that HSCARG may also target nuclear proteins, such as transcription factors, to further counter-balance the effects of the decreasing NADPH concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure study of TIP30, however, failed to provide structural evidence for these bioactivities [96]. Rather, the study revealed that TIP30 can bind NADPH, which may influence its function, and may directly bind and block the cargo binding position of Importin b, an essential shuttle protein for nucleocytoplasmic transport [77], in a Ran-GTP-independent manner [96]. In support of this structural notion, biochemical studies [89,97] have shown that TIP30 indeed inhibits nucleocytoplasmic transport mediated by Importin b in a Ran-GTP-independent manner.…”
Section: What Is Tip30?mentioning
confidence: 83%
“…On the other hand, other bioinformatic studies have suggested that TIP30 is related to short-chain dehydrogenases/reductases (SDR) [94,95]. The crystal structure study of TIP30, however, failed to provide structural evidence for these bioactivities [96]. Rather, the study revealed that TIP30 can bind NADPH, which may influence its function, and may directly bind and block the cargo binding position of Importin b, an essential shuttle protein for nucleocytoplasmic transport [77], in a Ran-GTP-independent manner [96].…”
Section: What Is Tip30?mentioning
confidence: 97%
“…Likewise, Gal3p, the transcriptional inducer in S. cerevisiae, demonstrates a ϳ90% sequence similarity to Gal1p, the bona fide galactokinase of the Leloir pathway that can, itself, function as a ligand sensor (24 -30). The molecular architecture of UDP-galactose 4-epimerase, another enzyme in galactose metabolism (31), has now been observed in NmrA, a negative transcriptional regulator in Aspergillus nidulans (32) and TIP30/CC3, a putative metastasis suppressor that promotes apoptosis (33). More than likely, other examples will be found where enzymatic scaffolds have been hijacked to serve in transcriptional regulation roles.…”
Section: Resultsmentioning
confidence: 99%